Pengaruh Beban Kerja dan Kompensasi Terhadap Kinerja Karyawan Rindang Coffee Shop di Palembang - Lulu Alfia Ramadani; Hamid Halin; Endah Dewi Purnamasari (CV. Ulil Albab Corp, 2024)
This research aims to determine the influence of workload and compensation on the performance of Rindang Coffee Shop employees in Palembang. The data used is primary data and secondary data. Data collection techniques include questionnaires, observations and interviews. The technique used for sampling was nonprobability sampling with a saturated sampling technique or quantitative method, so that the researcher took the entirepopulation, namely 30 employees. The instrument used in this research was Google Form. This research uses a questionnaire method (Questionnaire) with the aim of collecting data by filling out the questionnaire provided